Impact of Corticosteroids on the Proportions of Circulating Tfh Cell Subsets in Patients With Systemic Lupus Erythematous - Mao, Minjing; Xu, Shuqin; Lin, Lin; Dong, Danfeng; Xue, Minghui; He, Siwei; Cai, Gang (Frontiers in Medicine, 2022)
Objectives: The aim of this study was to analyze the distribution of Tfh in lupus patients, and the effects of steroid on circulating Tfh cells of patients. Methods: Circulating Tfh cell subsets were defined by multicolor flow cytometry as Tfh17, Tfh2 or Tfh1 among CXCR5+CD45RA-CD4+ T cells in the peripheral blood of 27 SLE patients and 20 gender and age-matched healthy controls. To test the effects of corticosteroid on the Tfh cells, PBMC harvested from both SLE and Healthy donors were cocultured with dexamethasone, and then analyzed by Flow cytometry. Results: The proportion of Tfh17 increased significantly in SLE patients than in healthy controls. Additionally, patients with an active disease had decreased the Tfh1 subsets than those with an inactive disease and healthy donors did. The frequency of Tfh2 associated with the proportion of circulating plasmablasts and level of anti-dsDNA. Dexamethasone reduces the percentage of Tfh2 while increase proportion of Tfh17 subset in the gated CXCR5+CD45RA-CD4+ T cells. Conclusions: our study describes the distribution of circulating Tfh cell subsets in lupus patients. Corticosteroids treatment not only down-regulated circulating Tfh cell proportions, but also altered the distribution of Tfh subsets in vivo and in vitro.